Indonesian Muslim Diaspora: Strengthening Cognitive Aspects and Competencies Regarding Islamic Heritage in Southeast Asia - Zuhri, Mishbah Khoiruddin; Safii, Safii; Sobirin, Mohamad (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
This study examined the cognitive aspects and competencies of the Indonesian Muslim diaspora in Southeast Asia through a community empowerment program to preserve Islamic heritage. Muslim communities in Southeast Asia have a historical relationship in the process of da'wah, Islamic culture, and the transmission of knowledge. Historical heritage in the form of mosques, tombs, kingdoms, and religious ceremonies is a potential for halal tourism and a challenge for the cultural conservation process. In this regard, the Indonesian Muslim diaspora plays a significant role in efforts to maintain Islamic heritage in Southeast Asia due to their shared culture, traditions, and language. Enhancing the diaspora's cognitive aspects and competencies was a priority for assistance. Therefore, various activities were implemented to improve their ability to document relevant information about Islamic heritage. This endeavor employed a Participatory Action Research (PAR) methodology to support the Indonesian diaspora residing in Malaysia, Thailand, and Brunei Darussalam. The mentoring program included Focused Group Discussions about Islamic heritage and assistance in improving skills related to data collection and writing about Islamic heritage and Arabic Pegon writing. Following the mentoring activities, notable improvements were observed in the cognitive aspects of the assisted subjects concerning historical mosques and Islamic kingdoms (13.3%), Islamic museums (21.43%), Islamic traditions (35.71%), and Islamic arts (42%), tombs (38.46%), and haul ceremonies (84%). Additionally, there was increased competency in searching and writing Islamic heritage information (13.3%) and Arabic Pegon writing (28.57%) after the mentoring. To ensure program sustainability, the diaspora actively disseminates service outcomes through online directories. Furthermore, ongoing collaboration is fostered through community-based cultural initiatives, which contribute to preserving Islamic history.